RESPIRATORY AND CIRCULATORY PROBLEMS OF COVID-19 IN THE CONTEXT OF ESTABLISHING INTENSIVE CARE UNIT NURSING DIAGNOSIS - Ika Ainur Rofi'ah; Muhammad Sajidin (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Introduction: The novel coronavirus disease 2019 (COVID-19) is a virus that attacks the respiratory tract with rapid spread and high mortality. Initial reports that COVID-19 associated with critical care due to the severity of the disease requiring mechanical assistive devices in its treatment. The purpose to identify the nursing diagnosis related to respiratory and circulatory problems of COVID-19 in the critical care unit. Method: An integrative review highlights the issue that nursing problems related to respiratory and circulatory in COVID-19 patients admitted to the Intensive Care Unit (ICU). This study focuses on papers published from 2020 to 2021 using the keyword "clinical manifestation of COVID-19" which was accessed through the Pubmed database. Result: The results showed that findings in articles that were reviewed and integrated with the SDKI. Nursing diagnosis related to respiratory problems such as 1) Ineffective airway clearance; 2) Dysfunctional ventilatory weaning response; 3) Impaired gas exchange; 4) Impaired spontaneous ventilation. Nursing diagnosis related to circulatory problems such as 1) Risk / decreased cardiac output; 2) Risk for bleeding; 3) Risk for effective renal perfusion; 4) Risk for ineffective cerebral perfusion. Conclusion: Critical care nurses carry out a series of treatments based on the nursing process stages, one of which is the enforcement of a nursing diagnosis. The nursing diagnosis is needed to develop nursing plans and strategies for implementation so that the goals of nursing care are achieved. Keywords: covid-19, nursing diagnosis, intensive care unit